The Influence of Value Proposition, Customer Perceived Value, Customer Engagement, and Delivery Process on Purchase Decisions of Kopi Kenangan Products in Bandar Lampung - Nadia Utami; Lestari Wuryanti; Ayu Nursari (Green Inflation: International Journal of Management and Strategic Business Leadership, 2026)
This study examines consumer purchase decisions toward Kopi Kenangan products in Bandar Lampung, focusing on the role of value proposition, customer perceived value, customer engagment, and delivery process. The growth of ready-to-drink coffee brands has increased competition, making it important to understand the factors that encourage consumers to choose a particular coffee brand. This study aims to analyze the partial and simultaneous effects of value proposition, customer perceived value, customer engagement, and delivery process on purchase decisions. A quantitative approach was applied using a survey method. Data were collected through an online questionnaire distributed to 400 Kopi Kenangan consumers selected using purposive sampling. The data were analyzed using validity and reliability tests, classical assumption tests, and multiple linear regression with SPSS. The findings show that value proposition, customer perceived value, customer engagement, and delivery process have positive and significant effects on purchase decisions. Simultaneously, these four variables also significantly influence consumer purchase decisions. The results indicate that purchase decisions are formed not only by product quality, but also by perceived benefits, brand interaction, and service convenience. This study contributes to marketing and consumer behavior literature and provides practical insights for improving coffee brand competitiveness.